Viability of Trade Credit as an Underlying Asset in a Shari’ah Compliant Alternative Credit System - Raheem, Mohamed Mahees; Meera, Ahamed Kameel Mydin; Adewale, Abideen (Journal of Islamic Finance, 2018)
Trade credit is a form of short term financing that is commonly utilised by firms, especially small and medium enterprises (SMEs) for working capital management purposes. As trade credit is unstructured and is variable and dependent upon each transaction, it makes it a highly illiquid asset/liability. This paper adopts a review of literature in order to identify if trade credit can be monetised and used as a medium of exchange. The advantages that such a system can bring are is manifold, mainly through providing an alternate source of liquidity for cash-strapped firms, boosting employment of resources, and a multiplier effect in terms of income and production. Upon initial analysis into the nature of trade credit, its modus operandi and the Shari’ah principles of bay al-Dayn, this conceptual paper posits that monetization of trade credits into an alternative currency, in accordance to the terms of the trade credit, is indeed possible and viable.